Photooxidation-induced fluorescence amplification system for an ultra-sensitive enzyme-linked immunosorbent assay (ELISA) - Heo, Youhee; Shin, Kwanwoo; Park, Min Cheol; Kang, Ji Yoon (Nature Publishing Group, 2021)
This report suggests a method of enhancing the sensitivity of chemifluorescence-based ELISA, using photooxidation-induced fluorescence amplification (PIFA). The PIFA utilized autocatalytic photooxidation of the chemifluorescent substrate, 10-acetyl 3,7-dihydroxyphenoxazine (ADHP, Amplex Red) to amplify the fluorescent product resorufin, initially oxidized by horse radish peroxidase (HRP). As the amplification rate is proportional to the initial level of resorufin, the level of antigen labeled by HRP is quantified by analyzing the profile of fluorescence intensity. The normalized profile was interpolated into an autocatalysis model, and the rate of increase at half-maximum time was quantified by the use of an amplification index (Al). The lower limit of detection, for resorufin or HRP, was less than one-tenth that of the plate reader. It requires only slight modification of the fluorescence reader and is fully compatible with conventional or commercial ELISA. When it is applied to a commercial ELISA kit for the detection of amyloid beta, it is verified that the PIFA assay enhanced the detection sensitivity by more than a factor of 10 and was compatible with a conventional 96-well ELISA assay kit. We anticipate this PIFA assay to be used in research for the detection of low levels of proteins and for the early diagnosis of various diseases with rare protein biomarkers, at ultra-low (pg/mL) concentrations.